EXPLORING ISLAMIC TRACES IN TAPANULI THROUGH THE BONGAL SITE: HISTORY, IDENTITY AND CULTURAL HERITAGE - Nurcintama Purba; Rhoma Dwi Aria Yuliantri; Awanis Akalili (SOSIOEDUKASI, 2026)
This study aims to identify and analyze the traces of Islam in Tapanuli through the Bongal Site, located in Jago-Jago Village, Badiri District, Central Tapanuli Regency, North Sumatra. The Bongal Site is an archaeological site containing significant artifacts dating from the 7th to the 10th century CE, including Umayyad and Abbasid dynasty coins, Islamic glass fragments, intaglios, beads, Middle Eastern ceramics, and Islamic medical instruments. This study employs a descriptive qualitative historical approach. Data were collected through field observations, artifact analysis, literature review, and in-depth interviews with an archaeologist-historian from Universitas Negeri Medan, the administrator of the Fansuri Museum at the Bongal Site, and the site owner. The findings reveal that the Bongal Site constitutes new evidence of the spread of Islam in Tapanuli, as indicated by artifacts suggesting the existence of trade networks and direct interaction with the Islamic world as early as the 7th century CE. The Bongal Site holds profound significance for the cultural identity and cultural heritage of the Central Tapanuli community. Drawing on Stuart Hall's cultural identity theory and the concept of cultural heritage, this study demonstrates that the Bongal Site is not merely an archaeological site, but an integral part of the collective identity of the local community that requires sustainable preservation.